Hyaluronic acid drives mesenchymal stromal cell-derived extracellular matrix assembly by promoting fibronectin fibrillogenesis. Issue 35 (12th March 2021) - Assunção, Marisa; Yiu, Chi Him Kendrick; Wan, Ho-Ying; Wang, Dan; Ker, Dai Fei Elmer; Tuan, Rocky S.; Blocki, Anna
Abstract : Hyaluronic acid (HA) is present at sites of ongoing fibronectin fibrillogenesis (fibrillar adhesions) and necessary for efficient fibronectin fibrillogenesis. As a result, fibronectin deposition can be enhanced by exogenous HA. Abstract : Hyaluronic acid (HA)-based biomaterials have been demonstrated to promote wound healing and tissue regeneration, owing to the intrinsic and important role of HA in these processes. A deeper understanding of the biological functions of HA would enable better informed decisions on applications involving HA-based biomaterial design. HA and fibronectin are both major components of the provisional extracellular matrix (ECM) during wound healing and regeneration. Both biomacromolecules exhibit the same spatiotemporal distribution, with fibronectin possessing direct binding sites for HA. As HA is one of the first components present in the wound healing bed, we hypothesized that HA may be involved in the deposition, and subsequently fibrillogenesis, of fibronectin. This hypothesis was tested by exposing cultures of mesenchymal stromal cells (MSCs), which are thought to be involved in the early phase of wound healing, to high molecular weight HA (HMWHA). The results showed that treatment of human bone marrow derived MSCs (bmMSCs) with exogenous HMWHA increased fibronectin fibril formation during early ECM deposition. On the other hand, partial depletion of endogenous HA led to a drastic impairment of fibronectin fibril formation, despite detectable granular presence of fibronectin in the perinuclear region, comparable to observations made under the well-established ROCK inhibition-mediated impairment of fibronectin fibrillogenesis. These findings suggest the functional involvement of HA in effective fibronectin fibrillogenesis. The hypothesis was further supported by the co-alignment of fibronectin, HA and integrin α5 at sites of ongoing fibronectin fibrillogenesis, suggesting that HA might be directly involved in fibrillar adhesions. Given the essential function of fibronectin in ECM assembly and maturation, HA may play a major enabling role in initiating and propagating ECM deposition. Thus, HA, as a readily available biomaterial, presents practical advantages for de novo ECM-rich tissue formation in tissue engineering and regenerative medicine.